STUDI KELAYAKAN RENCANA PENERAPAN E-TICKETING RORO BENGKALIS - Suharyono (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
The purpose of our research is to study the application of the Roro e-ticket information system from the aspect of user needs. In determining the variables of the e-ticket information system, quantitative methods will be carried out on aspects of customer needs, technical aspects using descriptive methods. The time of the research was carried out in 2022 for 4 months. Located in Roro Harbor, Bengkalis Regency. The number of samples in this study were 100 respondents who used roro in Bengkalis Regency. The research variables, namely: system quality (X1), service quality (X2), and user needs (Y). The results of this study have proven that partially or simultaneously the variables X1 (system quality) and X2 (service quality) affect the Y variable (user needs). The community of roro users in Bengkalis Regency hopes that the plan for implementing e-tickets in roro is no longer just a discourse but has yet to be realized. This is in accordance with the results of a survey that has been conducted. With the application of e-tickets, the roro crossing service in Bengkalis is increasingly optimal. However, the public hopes that the application of e-tickets will not affect the increase in ticket prices. Do not let the e-ticket, users are even burdened with additional costs.